Lived experience and virtual reality: visual method of analysis based on video recordings and the Valence-Arousal diagram - Charles-Alexandre Delestage; Willy Yvart (Sintaxis, 2024)
The specificity of Virtual Reality is that it offers the user almost complete sound and visual immersion, relying heavily on the sensation of presence, activated by audio and visual indications of the simulated space and strongly linked to the emotional dimension of the virtual reality experience. From the point of view of experience design research, since the user is immersed in a virtual world, real-time feedback on his or her experience is more difficult than for other media. The aim of this article is to present a visual qualitative approach to collecting traces of a virtual reality user's lived experience using a visual method protocol involving synchronous virtual real-world video recordings and the Spot Your Mood tool (Yvart, Delestage, Leleu-Merviel, 2016).